FcγRIIIa receptor interacts with androgen receptor and PIP5K1α to promote growth and metastasis of prostate cancer. Issue 13 (23rd January 2022) - Larsson, Per Flodbring; Karlsson, Richard; Sarwar, Martuza; Miftakhova, Regina; Wang, Tianyan; Syed Khaja, Azharuddin Sajid; Semenas, Julius; Chen, Sa; Hedblom, Andreas; Ali, Amjad; Ekström‐Holka, Kristina; Simoulis, Athanasios; et al.
Abstract : Low‐affinity immunoglobulin gamma Fc region receptor III‐A (FcγRIIIa) is a cell surface protein that belongs to a family of Fc receptors that facilitate the protective function of the immune system against pathogens. However, the role of FcγRIIIa in prostate cancer (PCa) progression remained unknown. In this study, we found that FcγRIIIa expression was present in PCa cells and its level was significantly higher in metastatic lesions than in primary tumors from the PCa cohort ( P = 0.006). PCa patients with an elevated level of FcγRIIIa expression had poorer biochemical recurrence (BCR)‐free survival compared with those with lower FcγRIIIa expression, suggesting that FcγRIIIa is of clinical importance in PCa. We demonstrated that overexpression of FcγRIIIa increased the proliferative ability of PCa cell line C4‐2 cells, which was accompanied by the upregulation of androgen receptor (AR) and phosphatidylinositol‐4‐phosphate 5‐kinase alpha (PIP5Kα), which are the key players in controlling PCa progression. Conversely, targeted inhibition of FcγRIIIa via siRNA‐mediated knockdown or using its inhibitory antibody suppressed growth of xenograft PC‐3 and PC‐3M prostate tumors and reduced distant metastasis in xenograft mouse models. We further showed that elevated expression of AR enhanced FcγRIIIa expression, whereas inhibition of AR activity using enzalutamide led to a significant downregulation of FcγRIIIa protein expression. Similarly, inhibition of PIP5K1α decreased FcγRIIIa expression in PCa cells. FcγRIIIa physically interacted with PIP5K1α and AR via formation of protein–protein complexes, suggesting that FcγRIIIa is functionally associated with AR and PIP5K1α in PCa cells. Our study identified FcγRIIIa as an important factor in promoting PCa growth and invasion. Further, the elevated activation of FcγRIII and AR and PIP5K1α pathways may cooperatively promote PCa growth and invasion. Thus, FcγRIIIa may serve as a potential new target for improved treatment of metastatic and castration‐resistant PCa. Abstract : Our findings show that FcγRIIIa promotes prostate cancer growth and invasion through its direct interaction with androgen receptor. There is also an interaction between FcγRIIIa in cancer cells and IgG immune complexes from the tumor‐associated microenvironment. The increased expression of FcγRIIIa may be required for the activation of the PIP5K1α/PI3K/AKT pathways in cancer cells during the progression from androgen‐dependent cancer to a castration‐resistant state.